2020
DOI: 10.6061/clinics/2020/e1486
|View full text |Cite
|
Sign up to set email alerts
|

Association between bile acid metabolism and bone mineral density in postmenopausal women

Abstract: OBJECTIVES: Previous studies have not shown any correlation between bile acid metabolism and bone mineral density (BMD) in women with postmenopausal osteoporosis. Thus, the current study evaluated the association between bile acid levels as well as BMD and bone turnover marker levels in this group of women. METHODS: This single-center cross-sectional study included 150 postmenopausal Chinese women. According to BMD, the participants were divided into three groups: osteoporosis group, osteopenia group, and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…Besides the modulation towards GM, different treatments also resulted in a considerable change of the fecal metabolites ( Supplementary Table S1 ). Bile acid is an important compound which has been reported to have vital roles in bone metabolism ( 48 , 49 ). The primary bile acid (e.g., cholic acid) is synthesized in liver and modified to secondary products such as lithocholic acid, deoxycholic acid and their conjugated species in gut by microbes, finally enters portal veins ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the modulation towards GM, different treatments also resulted in a considerable change of the fecal metabolites ( Supplementary Table S1 ). Bile acid is an important compound which has been reported to have vital roles in bone metabolism ( 48 , 49 ). The primary bile acid (e.g., cholic acid) is synthesized in liver and modified to secondary products such as lithocholic acid, deoxycholic acid and their conjugated species in gut by microbes, finally enters portal veins ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids Insufficient data. Positively correlated with BMD and negatively correlated with bone turnover biomarkers reflecting bone absorption in postmenopausal women [140].…”
Section: ↑[162-163]mentioning
confidence: 96%
“…Accumulating evidence has shown that levels of total fasting and postprandial plasma BA increase after SG and RYGB and it is thought that these changes contribute to improved lipid and glucose homeostasis, insulin sensitivity, and energy expenditure after BS [139]. BA also seem to have a metabolic effect on bone, with a study in postmenopausal women revealing that total serum BA was positively correlated with BMD, and negatively correlated with bone turnover biomarkers of bone resorption [140]. In addition, studies in mice found that the activation of the FXR BA receptor significantly promoted osteoblastic differentiation and that FXR agonists suppressed osteoclast differentiation from bone marrow macrophages.…”
Section: Acknowledged Factors For Future Lines Of Researchmentioning
confidence: 99%
“…On the other hand, treatment with lithocholic acid has been reported to decrease arthritis score in collagen II-induced arthritis mouse model along with suppressing inflammatory responses in RA patients ( Li Z. et al, 2019 ). Zhao et al reported that bile acids are positively correlated with BMD as osteoporotic and osteopenic post-menopausal women have significantly reduced levels of bile acids than healthy controls ( Zhao et al, 2020 ). It is observed that bile acids induce differentiation of osteoblasts via stimulation of farnesoid X receptor (FXR).…”
Section: Nexus Between Gut Microbiota and Bone Healthmentioning
confidence: 99%